Make Bayley III Scores Comparable between United States and German Norms—Development of Conversion Equations - Kosmann, Pauline; Blaeser, Annett; Rochow, Markus; So, Hon Yiu; Ascherl, Rudolf; Heussinger, Nicole; Haiden, Nadja; Fusch, Christoph; Rochow, Niels; on behalf of GTC Consortium (Neuropediatrics, 2023)
Aim Bayley Scales of Infant and Toddler Development (Bayley-III) determines scaled scores and converts these into composite scores. It was shown that applying the German and the U.S. manual leads to different results. This study aims to systematically analyze the differences between the U.S. and German Bayley-III version and to develop conversion equations.Methods This simulation study generated a dataset of pairs of U.S. and German Bayley-III composite scores (cognitive: n = 4,416, language: n = 240,000, motor: n = 314,000) by converting the same number of achievable tasks for 48 age groups. Bland–Altman plot and regression analyses were performed to develop conversion equations for all age groups.Results German and US Bayley-III scores demonstrate distinct slope and interception for cognitive, language, and motor composite scores. Lower developmental performance leads to higher composite scores with U.S. norms compared with German norms (up to 15 points). These differences varied between age groups. With newly developed conversion equations, the results can be converted (R2 > 0.98).Interpretation This study confirms systematic differences between U.S. and German Bayley test results due to different reference cohorts. Our data consider the full age range and add conversion equations. These findings need to be acknowledged when comparing Bayley Scores internationally.
Keywords: Bayley; children; comparison; neurodevelopment